Constructive alignment in university teaching. - Biggs, John (HERDSA Review of Higher Education v.1 p.5-22, 2014)
Constructive alignment (CA) is an outcomes-based approach to teaching in which the learning outcomes that students are intended to achieve are defined before teaching takes place. Teaching and assessment methods are then designed to best achieve those outcomes and to assess the standard at which they have been achieved. Although the general idea of CA has been around for some time, it is only recently that it has been implemented on a reasonably large scale. Part of the reason for this is that the massive expansion in tertiary education involves a diverse range of students and of teaching subjects so that teaching and assessment need to be reviewed on an institution-wide basis with emphasis upon outcomes at institutional, program and unit levels. CA provides a framework for adjusting teaching and assessment to address the attainment of those outcomes and the standards reached. Research indicates that CA is effective in this but it initially requires time and effort in designing teaching and assessment and, as a systems approach, it is important that supporting institutional policies and procedures are in place. The article provides examples from Hong Kong and Australian context. CA properly implemented enhances teaching and learning quality and thus, as a form of quality enhancement, subsumes forms of quality assurance that can often be counter-productive. [Author abstract, ed]